2003
DOI: 10.1034/j.1600-0765.2003.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Are there HLA combinations typical supporting for or making resistant against aggressive and/or chronic periodontitis?

Abstract: The present study elucidates the variety of HLA associations and therefore the difficulty to assign single HLA markers to periodontal disease. Susceptibility/resistance of both aggressive and chronic periodontitis may rather be influenced by particular HLA marker combinations. Associated HLA haplotypes may be of further importance for unknown gene loci representing a part of the genetic background for periodontitis. The different associations in aggressive and chronic periodontitis indicate different susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 34 publications
1
44
2
5
Order By: Relevance
“…A possibility that CD14-TT was primarily associated with periodontitis and secondarily with BD could not be neglected, because it was recently reported that CD14-TT genotype was associated with periodontitis (Laine et al 2005), although other reports showed no association with the CD14 polymorphism (James et al 2007) or signiWcantly higher frequency of CD14-C allele in female patients with periodontitis (Folwaczny et al 2004). Similar situation could be considered for the association with DRB1*1501, because several reports suggested the association of periodontitis with speciWc HLA alelels including DRB1*1501 (Ohyama et al 1996;Stein et al 2003) and DQB1*0602 (Ohyama et al 1996). It is quite interesting to note here that DRB1*1501-DQB1*0602 haplotype was reported to accelerate the T cell immune response to P. gingivalis (Takashiba et al 1999).…”
Section: Discussionmentioning
confidence: 86%
“…A possibility that CD14-TT was primarily associated with periodontitis and secondarily with BD could not be neglected, because it was recently reported that CD14-TT genotype was associated with periodontitis (Laine et al 2005), although other reports showed no association with the CD14 polymorphism (James et al 2007) or signiWcantly higher frequency of CD14-C allele in female patients with periodontitis (Folwaczny et al 2004). Similar situation could be considered for the association with DRB1*1501, because several reports suggested the association of periodontitis with speciWc HLA alelels including DRB1*1501 (Ohyama et al 1996;Stein et al 2003) and DQB1*0602 (Ohyama et al 1996). It is quite interesting to note here that DRB1*1501-DQB1*0602 haplotype was reported to accelerate the T cell immune response to P. gingivalis (Takashiba et al 1999).…”
Section: Discussionmentioning
confidence: 86%
“…HLA-A*24(9), HLA-B*35, DRB1*04 and DR51 showed higher frequency in our PLS patients than in controls, but the differences were not statistically significant. HLA-A*24(9) DRB1*04 and DR51 alleles have been associated with different kinds of periodontitis in other countries [33,51-53]. …”
Section: Discussionmentioning
confidence: 99%
“…HLA-9 ve HLA-15 antijenlerinin agresif periodontitisle ilişkili olduğu gösterilmiştir. 5,27 Yapılan başka bir calışmada HLA class I, HLA class II antijenleri ile periodontal hastalık arasında ilişki olduğunu gösterilmiştir. 28 Agresif periodontitis ile HLA-A2 ve HLA-B5 arasında ise negatif ilişki vardır.…”
Section: Agresi̇f Peri̇odonti̇ti̇s İçi̇n Ri̇sk Faktörleri̇ 1 Mikrobiyolojikunclassified